The Use of Diagnostic Musculoskeletal Ultrasound for the Evaluation of the Iliopsoas in the Anterior Hip: A Guide for Rehabilitation Providers - Robert C. Manske; Michael Voight; Chris Wolfe; Phil Page; Beth Bardowski (International Journal of Sports Physical Therapy)
Musculoskeletal ultrasound (MSK-US) has become an increasingly valuable tool in the evaluation and management of soft tissue and joint pathologies, particularly for rehabilitation providers. This article highlights the use of MSK-US for assessing the iliopsoas tendon and musculature in the anterior hip. The iliopsoas complex is often implicated in conditions such as tendinitis, snapping hip syndrome, and hip flexor strains, and accurate assessment can be challenging due to its deep anatomical location. MSK-US offers a safe, cost-effective, and dynamic modality for visualizing the iliopsoas, providing crucial insights into its morphology, pathology, and response to rehabilitation interventions. This paper discusses the anatomy of the iliopsoas, ultrasound scanning techniques, common findings, and the clinical relevance of MSK-US in rehabilitation settings. This paper explores the efficacy of MSK-US in the assessment of the iliopsoas muscle and tendon and underscores its utility in diagnosing iliopsoas-related abnormalities such as tendinopathy and bursitis.